To simplify the expression \( \sqrt{28} + \sqrt{28} + \sqrt{28} \), you can combine the three square roots of 28.
\[ \sqrt{28} + \sqrt{28} + \sqrt{28} = 3\sqrt{28} \]
Next, we can simplify \(\sqrt{28}\): \[ \sqrt{28} = \sqrt{4 \times 7} = \sqrt{4} \cdot \sqrt{7} = 2\sqrt{7} \]
Now substituting back: \[ 3\sqrt{28} = 3 \times 2\sqrt{7} = 6\sqrt{7} \]
Thus, the simplified sum is: \[ 6\sqrt{7} \]
If we look at the options provided, it appears they were not formatted very clearly, but the answer \( 6\sqrt{7} \) is not directly noted. Given no exact match, it should be noted that this sum could potentially correspond to the simplified expression, depending on any potential formatting or typographical errors in the answer choices mentioned.